Inorganic Acids, Fluoridated Ethanol’s, and Some Fluoridated Saturated Hydrocarbons’ Stability and Bond Dissociation Energy Values. - Abdel-Wahab, Hebah (European Journal of Applied Sciences, 2023)
The energetics of chemical processes can be assessed using bond dissociation energy values. The objective of this work is to calculate the hydrogen-halogen (H-X) and carbon- fluorine (C-F) bond dissociation energy values for some energetic materials including fluorinated ethanols, some fluorinated saturated hydrocarbons, and some inorganic acids. Bond dissociation energy values for 40 different compounds are reported in this work. All calculated bond dissociation energy is reported for standard conditions, 1 atm pressure and 298 K temperature. Bond dissociation energy values are listed in tables 1,2 and 3.